Daguerre's Abstraction. (3rd May 2016) - Bate, David
Abstract : The understanding of abstraction in so-called Western art theory is usually a narrative 'towards' purism or universalism. The impact of photography on these discourses is usually related to this in its function of representational realism, and attempt to join modernist discourses through a tern to abstraction. Photography is more rarely examined in terms of its contribution to abstraction. This paper turns to that question by looking at the early role of photography in constructing abstraction, notably in pictures made by Louis Daguerre.